2012
DOI: 10.2527/jas.2011-4753
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fat deposition and fat removal genes is associated with intramuscular fat content in longissimus dorsi muscle of Korean cattle steers1

Abstract: Intramuscular fat (IMF) in cattle is an important component of traits that influence meat quality. We measured carcass characteristics and gene expression in Korean steers to clarify the molecular mechanism(s) underlying IMF deposition in LM tissue by determining the correlation between IMF content and gene expression abundance and by developing models to predict IMF content using gene expression abundance. The deposition of IMF is determined by a balance between fat deposition and fat removal in the LM. We me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 31 publications
11
81
2
3
Order By: Relevance
“…CIDEA , THRSP , ACSM1 , DGAT2 and FABP4 from the TAG gene set were selected based on their combined ranking in both the cattle and sheep correlation datasets (Table 2). Consistent with our findings, two of these five genes ( DGAT2 and FABP4 ) have also been identified to be correlated with IMF in cattle previously [26,27]. We tested the top 2, top 3, top 4 and top 5 genes above (defined as the “IMF 2–5 gene sets”) to determine whether combinations of the top genes had a higher correlation with IMF% in both species than CIDEA alone.…”
Section: Resultssupporting
confidence: 85%
“…CIDEA , THRSP , ACSM1 , DGAT2 and FABP4 from the TAG gene set were selected based on their combined ranking in both the cattle and sheep correlation datasets (Table 2). Consistent with our findings, two of these five genes ( DGAT2 and FABP4 ) have also been identified to be correlated with IMF in cattle previously [26,27]. We tested the top 2, top 3, top 4 and top 5 genes above (defined as the “IMF 2–5 gene sets”) to determine whether combinations of the top genes had a higher correlation with IMF% in both species than CIDEA alone.…”
Section: Resultssupporting
confidence: 85%
“…As the amount of triglyceride within the adipocyte increases, the total proportion of SFA also increases in relation to other ones [41]. An increase in DGAT2 gene expression was previously demonstrated to be associated with an increase in the amount of intramuscular fat [42]. Thus, these results demonstrate that DGAT2 gene contributed to the accumulation of SFA in the intramuscular tissue during the finishing phase (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…It may also used to treat pain caused by nerve damage in people with diabetes [2]. DL is considered among the most important antidepressant drugs therefore, the development of reliable rapid and accurate procedures for this active ingredient quantification is welcomed [3]. A survey of literature showed that several analytical methods have been reported for determination of DL in its pure form, pharmaceutical preparations and biological fluids, where DL is not determined officially in any pharmacopoeia.…”
Section: Introductionmentioning
confidence: 99%